Management of dysmenorrhea through yoga: A narrative review - Kanchibhotla, Divya; Subramanian, Saumya; Singh, Deeksha (Frontiers in Pain Research, 2023)
Menstrual pain also known as dysmenorrhea is one of the most common and underrated gynecological disorders affecting menstruating women. Although the symptoms and impact might vary greatly, it is defined by cramps in the lower abdomen and pain that radiates to lower back and thighs. In some cases it is also accompanied by nausea, loose stool, dizziness etc. A primary narrative review was conducted on the impact of yoga on dysmenorrhea experienced by women. The English-language literature published until 2022 was searched across databases such as PubMed, Google Scholar and Scopus. “Yoga” and “menstrual pain” OR “dysmenorrhea” were used as keywords for the search across several databases. A total of 816 title searches were obtained across all the database searches. This review article included 10 studies based on the selection criteria. The studies examined the impact of a varied set of 39 asanas, 5 pranayamas and Yoga nidra on dysmenorrhea. The studies demonstrated a significant relief in dysmenorrhea among those who practiced Yoga (asanas/pranayama/yoga nidra) with improved pain tolerance and reduced stress levels. Regulating the stress pathways through yoga was found to be a key in regulating hormonal balance and reduction in dysmenorrhea.